2018
DOI: 10.1055/s-0038-1627474
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Density Predicts Facial Nerve Outcome and Tumor Growth after Subtotal Resection of Vestibular Schwannoma

Abstract: Vestibular schwannoma (VS) behavior following subtotal resection (STR) is highly variable. Overall progression rates have been reported as high as 44%, and optimal treatment is controversial. Correspondingly, identification of a reliable clinical or pathologic marker associated with progression after STR would help guide decision-making. A prospectively maintained institutional VS registry from 1999 to 2014 was retrospectively reviewed for sporadic VS patients who underwent primary STR without preceding stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Although the composition varies with each tumor, immune cells can infiltrate the TME and take on several roles that promote and/or resist inflammation and tumor proliferation. 24 Although the mechanisms have not been fully elucidated, several studies have found associations between TAMs, tumor growth, and HL in VS. 5 , 22 , 25 - 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the composition varies with each tumor, immune cells can infiltrate the TME and take on several roles that promote and/or resist inflammation and tumor proliferation. 24 Although the mechanisms have not been fully elucidated, several studies have found associations between TAMs, tumor growth, and HL in VS. 5 , 22 , 25 - 28 …”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective investigation of 46 patients with VS with subtotal resections, Graffeo et al 25 found that higher macrophage density (defined as the ratio of CD68 + macrophages to S100 + cells) was significantly associated with tumor progression postoperatively. However, it was unknown whether M1 and/or M2 macrophages were implicated, as CD68 is a nonspecific pan-macrophage marker.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to gather individual patient-level data for 349 patients from 6 studies (Table 2). 2,12,13,17,18,20 The range of Ki-67 index values for patients with recurrence was 1.4-4.8%, whereas the range for patients without recurrence was 0.6-1.9%.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…31 Graffeo et al and Kontorinos et al showed that there are increased immune cells in VSs that have more rapid growth. 12,29 Graffeo et al demonstrated that tumors with higher S100 and CD68 macrophages tended to have a more aggressive growth pattern after subtotal resection. 12 These results have…”
Section: Ki-67 Index and The Role For Prognostication In Vs Managementmentioning
confidence: 99%
“…1,7,[11][12][13] The principal factor determining VII nerve damage at the time of surgical resection is the size of the VS itself, with tumor vascularity, the tumour micro-environment and tumour consistency also playing a part. [14][15][16][17][18][19][20] Patients with VSs associated with neurofibromatosis type-2 also seem to be at risk of adverse VII nerve outcomes following surgical resection. 21 With smaller tumors (<20mm), rates of VII nerve palsy following VS resection are less than 10%, 16,19 but for larger tumors (>30mm) VII nerve function is affected in more than half of patients undergoing surgical resection.…”
Section: Facial (Vii) Nerve Weaknessmentioning
confidence: 99%